2017
DOI: 10.2131/jts.42.267
|View full text |Cite
|
Sign up to set email alerts
|

Joint toxicity of fluoroquinolone and tetracycline antibiotics to zebrafish (<i>Danio rerio</i>) based on biochemical biomarkers and histopathological observation

Abstract: -Herein, we report on the joint toxicity of four fluoroquinolones and two tetracyclines (β-diketone antibiotics-DKAs) to zebrafish based on a series of toxicological endpoints and histopathological observations. A positive dose-dependence was observed in DKA-exposure groups with a 72-hpf EC 50 of 130.3 mg/L for hatching rate, 120-hpf LC 50 of 149.8 mg/L, and 120-hpf EC 50 of 135.1 mg/L for malformation rate. When zebrafish at 60 dpf were exposed to a series of DKA concentrations (45, 60 and 90 mg/L) for 7, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
(55 reference statements)
3
12
0
Order By: Relevance
“…They demonstrated that TCs played a key role in the mixtures, and their simultaneous presence mainly had antagonistic actions. A similar result has been reported by Ding et al [ 38 ], with the TCs having a stronger effect than the DKAs, as the 120 hpf LC50 value for the malformation rate due to the exposure to the antibiotic mixtures was 149.8 mg/L, and for TCs, it was 18.3 mg/L. In contrast with previous results, the joint antibiotic toxicity of sulfamonomethoxine, cefotaxime sodium, tetracycline and enrofloxacin was more severe than that of a single treatment [ 83 ].…”
Section: Effects Of Antibiotic Mixtures In Zebrafishsupporting
confidence: 91%
See 2 more Smart Citations
“…They demonstrated that TCs played a key role in the mixtures, and their simultaneous presence mainly had antagonistic actions. A similar result has been reported by Ding et al [ 38 ], with the TCs having a stronger effect than the DKAs, as the 120 hpf LC50 value for the malformation rate due to the exposure to the antibiotic mixtures was 149.8 mg/L, and for TCs, it was 18.3 mg/L. In contrast with previous results, the joint antibiotic toxicity of sulfamonomethoxine, cefotaxime sodium, tetracycline and enrofloxacin was more severe than that of a single treatment [ 83 ].…”
Section: Effects Of Antibiotic Mixtures In Zebrafishsupporting
confidence: 91%
“…In accordance with the results of the previous study, Qiu et al [ 83 ] indicated that treatment with sulfonamide β-lactamtetracycline and quinolone antibiotics could affect the ROS content in zebrafish larvae. Changes in creatine kinase activity and creatinine concentration, which are related to muscle contraction and energy transfer, were observed in zebrafish after exposure to a series of DKA concentrations [ 38 ].…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that elderly patients taking cholesterol lowering drugs (Zocor, Lipitor, etc.) have shown drug–drug interactions (DDI), particularly with the anti-lipidemic drug Lopid (gemfibrozil [53,106]), but also with certain antibiotic classes, such as macrolides [107,108] and fluoroquinolones [109,110] and the heart medication, Nexteron (amiodarone) [64,111]. All of these drugs have been shown to cause mitochondrial toxicity by targeting a variety of, as well as multiple, mitochondrial mechanisms/targets.…”
Section: Polypharmacy In the Geriatric Populationmentioning
confidence: 99%
“…However, in a Zebrafish model ( Danio rario ), Ding et al found that TETRA induced damage at several concentrations (45, 60 and 90 mg/L) after 7, 14 and 21 days with mitochondrial damage, including diminished mitochondrial cristae and mitochondrial swelling. 32 Another study in hepatocytes showed significant negative influences on mitochondrial calcium uniporter with treatment after TETRA derived compounds (50 uM, 22.22 g). TETRA prevented Ca 2+ uptake by mitochondria and then inhibited the inducement of mitochondrial permeability transmission by Ca 2+ .…”
Section: Discussionmentioning
confidence: 98%